Performance of the RadonEye Monitor - Peter Bossew (Atmosphere)
In addition to cheap track-etch and expensive research-grade radon monitors, for several years, a new generation of affordable consumer-grade active monitors has been available. Their performance raises the question of whether they could also be used for certain objectives in a scientific context. This requires particular QA/QC as well as understanding their behavior and their limitations. This paper reports experiences with the RadonEye acquired over approximately two years, mainly for recording time series of radon concentration indoors and outdoors. Specific topics include calibration uncertainty, assessed by recording parallel time series; response to thoron by exposing the monitor to thorium-bearing material; and some unresolved questions related to measurement statistics to date. The main results are that factory calibration is quite uncertain and that sensitivity to thoron has to be considered in practical usage. Some identified statistical issues regarding the occurrence of anomalies and possible non-Poisson uncertainty remain unresolved.